The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1152/ajpgi.00180.2014
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 5b loss of function leads to defects in polarized signaling: implication for microvillus inclusion disease pathogenesis and treatment

Abstract: Microvillus inclusion disease (MVID) is an autosomal recessive condition resulting in intractable secretory diarrhea in newborns due to loss-of-function mutations in myosin Vb (Myo5b). Previous work suggested that the apical recycling endosomal (ARE) compartment is the primary location for phosphoinositide-dependent protein kinase 1 (PDK1) signaling. Because the ARE is disrupted in MVID, we tested the hypothesis that polarized signaling is affected by Myo5b dysfunction. Subcellular distribution of PDK1 was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 59 publications
(74 reference statements)
2
43
2
Order By: Relevance
“…Atypical PKC and Par6B show aberrant localization in IEC of individuals with microvillus inclusion disease carrying MYO5B mutations (Dhekne et al 2014;Kravtsov et al 2014;Michaux et al 2015), which is in agreement with a reported role for apical recycling endosomes in the regulation of the subcellular distribution of these polarity proteins (Golachowska et al 2010;Dhekne et al 2014). The mislocalization of aPKC-iota from the subapical domain of IEC was associated with impaired activation of ezrin at the apical surface and consequent impaired brush-border development (Dhekne et al 2014).…”
Section: The Crumbs3/patj/pals1 Complexsupporting
confidence: 84%
See 1 more Smart Citation
“…Atypical PKC and Par6B show aberrant localization in IEC of individuals with microvillus inclusion disease carrying MYO5B mutations (Dhekne et al 2014;Kravtsov et al 2014;Michaux et al 2015), which is in agreement with a reported role for apical recycling endosomes in the regulation of the subcellular distribution of these polarity proteins (Golachowska et al 2010;Dhekne et al 2014). The mislocalization of aPKC-iota from the subapical domain of IEC was associated with impaired activation of ezrin at the apical surface and consequent impaired brush-border development (Dhekne et al 2014).…”
Section: The Crumbs3/patj/pals1 Complexsupporting
confidence: 84%
“…In addition, the spatial distribution of endosomal system provides polarized signaling platforms (Bryant et al 2010;Dhekne et al 2014;Kravtsov et al 2014) that control the activation of ezrin at the apical surface of intestinal epithelial cells and, thereby, the development of the apical brush-border membrane (Dhekne et al 2014). Within the complex endosomal system (Perret et al 2005;Bay et al 2015), two endosomal subcompartments have been identified that appear particularly important for the correct sorting and trafficking of apical and basal proteins: the apical recycling endosome (ARE) and the common recycling endosome (CRE) (Fig.…”
Section: A Brief Introduction To Epithelial Cell Polarity In the Intementioning
confidence: 99%
“…MYO5B KD cells were generated with MYO5B mRNA targeted shRNA (NM_ 001080467) delivered by a pLKO.1-Puro-based lentiviral system and maintained with a selection marker puromycin (12 g/ml; Cayman Chemical, Ann Arbor, MI). Cells were transduced to stably express either scrambled or MYO5B-targeting shRNA (32). C2BBe cells at passage number 15 or less were grown on 100-mm dishes (Corning, Corning, NY) to ϳ70 -90% confluency and then subjected to reverse transduction (cells were seeded in the titrated viral medium supplemented with 8 g/ml Polybrene at 1:2 ratio; Millipore, Waltham, MA).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Lysates were centrifuged at 12,000 rpm for 15 min at 4°C. Protein concentrations were determined from supernatants, samples were eluted with 2ϫ Laemmli sample buffer (BioRad, Hercules, CA), and equivalent protein loads were analyzed by PAGE as before (11,32).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…MYO5B functions as a homodimer and has three functional domains: an N-terminal motor domain, a calmodulin-binding domain, and a C-terminal tail, which binds cargo through association with the small GTPases RAB8A and/or RAB11A (12, 13). Altered expression of myosin Vb affects the apical membrane trafficking mechanism in epithelial cells, causing mislocalization of apical brush border proteins, such as villin (vil), CD10, or alkaline phosphatase (ALP) in the cytoplasm of duodenal enterocytes (2, 3, 5), and an increased apical localization of transferrin receptor (5,14).Although mouse models mimicking certain features of MVID have previously been described, such as Rab8 (15), Cdc42 (16, 17), and Rab11a knockout (KO) mice (18,19), no mutations in the coding regions of those genes have been reported in human MVID patients. Current in vitro models to study apical trafficking and polarization-associated diseases such as MVID are the parental Caco2 cell line, Caco-BBE, and LS174 W4 cells, in which polarization can be induced in vitro (4,8,12, 20).…”
mentioning
confidence: 99%